Civilization of nomads: Attila in the history of the Hun tribes - Alzhanbaeva, U.; Zhumadіlova B. (Journal of Oriental Studies, 2024)
This article discusses the history of the Hun tribes that have managed to create the first state of nomads in the historical arena, and describes their way of life and culture, public and political structure, military art and historical migration. However, the authors of this work characterize the leader of the Huns as an outstanding historical figure. We know that Attila was not only the ruler of the Huns state, but many researchers of the time wrote about his skills in the management of public affairs, as well as a person who first introduced the West specifics of the steppe policy